2012
DOI: 10.1007/s11051-012-1029-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of risk-based nanomaterial groups for occupational exposure control

Abstract: Given the almost limitless variety of nanomaterials, it will be virtually impossible to assess the possible occupational health hazard of each nanomaterial individually. The development of science-based hazard and risk categories for nanomaterials is needed for decision-making about exposure control practices in the workplace. A possible strategy would be to select representative (benchmark) materials from various mode of action (MOA) classes, evaluate the hazard and develop risk estimates, and then apply a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 61 publications
2
97
0
4
Order By: Relevance
“…Physico-chemical properties of nanomaterials that have been recognized to influence their inhalability, deposition efficiency, and toxicology are their airborne and hydrodynamic size, size distribution, shape (and aspect ratio), their state of agglomeration, surface properties and functionalization (surface area, porosity, charge, reactivity, chemistry/ coatings, contaminants), as well as solubility and crystallinity (Kuempel et al, 2012;Nel et al, 2013a;Oberdörster, 2009;Oberdörster et al, 1994;Rodriguez-Yanez et al, 2013;Zhu et al, 2013). Also in in vitro cytotoxicity assays, particle size, surface chemistry and coating, as well as chemical composition have been recognized as key determinants of nanoparticle adverse effects (Feltis et al, 2012;Horev-Azaria et al, 2011;Kroll et al, 2011).…”
Section: Particle Characteristics Influencing Particle Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physico-chemical properties of nanomaterials that have been recognized to influence their inhalability, deposition efficiency, and toxicology are their airborne and hydrodynamic size, size distribution, shape (and aspect ratio), their state of agglomeration, surface properties and functionalization (surface area, porosity, charge, reactivity, chemistry/ coatings, contaminants), as well as solubility and crystallinity (Kuempel et al, 2012;Nel et al, 2013a;Oberdörster, 2009;Oberdörster et al, 1994;Rodriguez-Yanez et al, 2013;Zhu et al, 2013). Also in in vitro cytotoxicity assays, particle size, surface chemistry and coating, as well as chemical composition have been recognized as key determinants of nanoparticle adverse effects (Feltis et al, 2012;Horev-Azaria et al, 2011;Kroll et al, 2011).…”
Section: Particle Characteristics Influencing Particle Effectsmentioning
confidence: 99%
“…Also in vivo, ZnO NM effects are reported being caused by dissolved ions (Kuempel et al, 2012), as recorded by increased LDH levels in the bronchoalveolar fluid (BALF; Kao et al, 2012). Klein et al (2012) found short-term inhalation exposure to 2.5 and 12.5 mg/m 3 Z-COTE® HP1 to increase inflammatory parameters in the BALF in a concentrationdependent manner.…”
Section: Comparison Of Nm Effects In the Pclus Test System To In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…determining the health risk). The banding strategies developed for nanomaterials have been recently reviewed [20], and approaches to link quantitative risk assessment with exposure control banding schemes (for categorical decision-making and validation) have been described [21].…”
Section: Societal Level Risk Managementmentioning
confidence: 99%
“…It is unlikely that it will be possible to assess toxicologically (using animal studies) all the ENMs in, or entering, commerce [21,36,37]. Therefore, it may be necessary to screen materials individually or as categories and assign them to hazard and control categories (based on physical-chemical parameters).…”
Section: Need To Develop Categorical Oelsmentioning
confidence: 99%